KEPENTINGAN INDONESIA DALAM MENGINISIASI PEMBENTUKAN ASEAN OUTLOOK ON INDO-PACIFIC (AOIP) TAHUN 2017 - Wulandari, Komang Triana; Sushanti, Sukma; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This study aims to analyze Indonesia's interests in initiating the ASEAN Outlook on Indo-Pacific in fulfilling Indonesia's grand strategy to become the world's maritime axis using qualitative methods. Regional geopolitical changes that have created a desire for countries to take part in Asia, including the United States and China with various cooperation formed to meet their respective interests. Indonesia on the other hand sees the country's potential as a strong maritime axis with adequate natural resources and strategic geographic potential in the Indo-Pacific region. However, Indonesia's desire is considered to be releasing ASEAN as one of the organizations in the region which is also a forum for Indonesia's foreign policy so far. Indonesia's desire to continue to spread its wings in the international arena without leaving ASEAN as a regional organization creates dynamics that trigger new ideas that are seen by Indonesia as a way to achieve its interests. Kata Kunci : Indonesia, ASEAN, Indo-Pacific, National Interest, ASEAN Outlook